Endoscopic versus external dacryocystorhinostomy: temporal and regional trends in the United States Medicare population. (2nd November 2019) - Kshirsagar, Rijul S.; Vu, Priscilla Q.; Liang, Jonathan
ABSTRACT: Purpose : Endoscopic surgeries, such as dacryocystorhinostomy (DCR), are increasingly performed for orbital and lacrimal conditions. This study describes and compares recent trends in endoscopic DCR with open, or external, DCR in the United States (US). Methods : Medicare-Part-B National Summary data files were analyzed from 2000 to 2015 for temporal and geographic trends in endoscopic and external DCR. Medicare Physician and Other Supplier public use files detailing provider information were collected and analyzed from 2012 to 2015. Results : Between 2000 and 2015, the number of external DCRs remained relatively unchanged (8008 to 7086, −0.7% average annual growth), while the number of endoscopic DCRs steadily increased (881 to 1674, 4.6% average annual growth). The greatest number of endoscopic DCRs were performed in the South Atlantic region, whereas the Mountain region had the greatest number per capita. From 2000 to 2015, the average payment per procedure for external DCR was 526.63, compared with 512.45 for endoscopic DCR. Of endoscopic DCRs performed from 2012 to 2015, 831 (79%) were performed by Ophthalmology, 184 (18%) were performed by Otolaryngology, and the remainder by other subspecialties. Conclusions : The number of endoscopic DCR surgeries increased over the last 15 years while the number of external DCR surgeries remained stable and continued to surpass endoscopic procedures. While ophthalmologists perform the overwhelming majority of endoscopic DCR, otolaryngologists are performing a growing number.